Novel SIX6 mutations cause recessively inherited congenital cataract, microcornea, and corneal opacification with or without coloboma and microphthalmia - ELÇİOĞLU, HURİYE NURSEL; ÇERMAN, EREN (My University, 2022)
Purpose: To investigate the molecular basis of recessively inherited congenital cataract, microcornea, and corneal opacification with or without coloboma and microphthalmia in two consanguineous families. Methods: Conventional autozygosity mapping was performed using single nucleotide polymorphism (SNP) microarrays. Whole-exome sequencing was completed on genomic DNA from one affected member of each family. Exome sequence data were also used for homozygosity mapping and copy number variation analysis. PCR and Sanger sequencing were used to confirm the identification of mutations and to screen further patients. Evolutionary conservation of protein sequences was assessed using CLUSTALW, and protein structures were modeled using PyMol. Results: In family MEP68, a novel homozygous nucleotide substitution in SIX6 was found, c.547G>C, that converts the evolutionarily conserved aspartic acid residue at the 183rd amino acid in the protein to a histidine, p.(Asp183His). This residue mapped to the third helix of the DNA-binding homeobox domain in SIX6, which interacts with the major groove of double-stranded DNA. This interaction is likely to be disrupted by the mutation. In family F1332, a novel homozygous 1034 bp deletion that encompasses the first exon of SIX6 was identified, chr14:g.60975890_60976923del. Both mutations segregated with the disease phenotype as expected for a recessive condition and were absent from publicly available variant databases. Conclusions: Our findings expand the mutation spectrum in this form of inherited eye disease and confirm that homozygous human SIX6 mutations cause a developmental spectrum of ocular phenotypes that includes not only the p
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Medicine; Health Sciences; Surgery Medicine Sciences; Eye Diseases and Surgery; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); GÖZ HASTALIKLARI; Klinik Tıp; Klinik Tıp (MED); BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); OPHTHALMOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Klinik Biyokimya; Kanser Araştırmaları; Moleküler Biyoloji; İlaç Keşfi; Yaşlanma; Genel Biyokimya, Genetik ve Moleküler Biyoloji; Biyokimya; Yapısal Biyoloji; Oftalmoloji; Optometri; Biochemistry, Genetics and Molecular Biology (miscellaneous); Clinical Biochemistry; Cancer Research; Molecular Biology; Drug Discovery; Aging; General Biochemistry, Genetics and Molecular Biology; Biochemistry; Structural Biology; Ophthalmology; Optometry